Implications of water resources distribution in Indonesia (Islamic perspective): A phenomenological paradigm approach. - Galuh, Ajeng Kartika (Universiti Sains Malaysia, 2014)
Several regions in Indonesia began to feel difficulty in obtaining access to water for agricultural, horticultural or evenfor their daily needs. Scarcity of water resources that occurred as a potential source conflicts. A phenomenological paradigm approach is used to interpret the phenomenon of water resources distribution in Indonesia.